Reconstruction of the Principles of Justice in Employment Agreements Post Constitutional Court Decision No. 168/PUU-XXI/2023 - Muhidin Muhidin; Faisal Santiago (Greenation Research & Yayasan Global Resarch National, 2025)
The Constitutional Court (MK) Decision No. 168/PUU-XXI/2023 marks a significant milestone in the development of labor law in Indonesia, particularly concerning Fixed-Term Employment Agreements (Perjanjian Kerja Waktu Tertentu or PKWT). The ruling sets a maximum duration for the implementation of PKWT at five years, including all possible extensions during the employment period. This time limit aims to provide legal certainty while ensuring maximum protection for workers employed under PKWT, who have often faced uncertainty and vulnerability in industrial relations. Issued on October 31, 2024, the MK decision strengthens the principle of justice in industrial relations by offering clearer and better protection for PKWT workers. With the five-year cap, workers are no longer subjected to prolonged uncertainty regarding their employment status, securing their rights more definitively. The ruling also balances employers’ authority to regulate employment relationships, allowing the use of PKWT under clear restrictions without arbitrary and unlimited contract renewals. This decision presents challenges for employers in adapting their contract practices to comply with the new regulations, especially in managing PKWT workers for short-term operational needs. MK Decision No. 168/PUU-XXI/2023 provides a stronger legal foundation to realize justice and legal certainty for workers, fostering harmonious, fair, and sustainable industrial relations, particularly for workers under PKWT status.